Haemangioendotheliosarcoma of the heart. Diagnosis and treatment. Issue 6 (December 1979) - Bjerregaard, P; Baandrup, U
Abstract : A case of haemangioendotheliosarcoma of the right atrium in a 28-year-old man is reported. The presence of a continuous murmur to the right of the sternum as a clue to the diagnosis is pointed out, and the usefulness of cardiac catheterisation and angiography in making diagnosis emphasised. Irradiation therapy with cobalt-60 had a palliative effect upon this malignant tumour.